#TITLE_ALTERNATIVE# - KURNIAWAN (NIM 10203043), CHRISTIAN
One of the efficient face recognition technique is Eigenface. It involves obtaining principal component (PCA) from a face database. These principal component are representaton of the face set. Any new face image can be represented as a linear combination of these eigenfaces. Face recognition process is begin with preparing database with various faces, then followed by making eigenface from those database. Image that will be tested should be normalized first. After that normalized face image will be projected to eigenface. The system will do recognition process based on existing database. It will give decision to that input regarding its euclidian distance.